Ovum-Pick Up and In Vitro Embryo Production Responses in Stimulated and Non-Stimulated Sahiwal Cows - Chandra, Pradeep; Kumar, Brijesh; Donadkar, Manoj M; rathi, Bhagi; Jasrotia, Nancy; Chouhan, Vikrant Singh; Kharayat, Nitish Singh; Singh, Sanjay Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The aim of the present study was to evaluate follicular population, oocyte recovery, quality, and in vitro embryo developmental competence in non-stimulated and FSH stimulated Sahiwal cows subjected to ovum pick-up (OPU) and in vitro embryo production (IVEP). The study was conducted on total 16 cows divided into two groups; group 1 FSH stimulated (n=08) and group 2 non-stimulated (n=08) Sahiwal cows. A total of 16 OPU sessions were performed in early luteal phase of estrous cycles. The mean number of follicles aspirated (17.13±1.87 Vs. 12.38±0.85) and the mean number of oocytes recovered (10.25±0.98 Vs. 6.75±0.60) per OPU per animal were significantly (p<0.05) higher in FSH-stimulated as compared to the non-stimulated cows. In stimulated group, a significantly (p<0.05) high Grade-A oocytes were recovered as compared to the non-stimulated group (60.98±0.49% Vs. 24.07±0.40%). However, maturation rate (84.41 Vs. 81.10%) and fertilization rate (78.46 Vs. 72.08) did not differ significantly between stimulated and non-stimulated groups. Further when fertilized oocytes were cultured in vitro for 7 days higher (p<0.05) cleavage rate (73.44%Vs. 61.25%) and embryo production (4.50±0.50 Vs. 2.38±0.43 per OPU session) were recorded in stimulated cows as compared to the non-stimulated cows. Further all the zygotes cleaved into 2-cell stage in both the groups, but subsequently significantly (p<0.05) more 4-cell stage, 8-cell stage and numerically higher 16-cell stage and compact morula (13.89% Vs. 5.26%) were recorded in stimulated than in non-stimulated Sahiwal cows. In conclusion, the FSH pre-stimulation prior to OPU-IVF increased the number of medium and large follicles, oocyte recovery and embryo quality in Sahiwal cows.